2020
DOI: 10.1508/cytologia.85.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation on Mitosis and Meiosis Anomalies and Agronomic Features in M2 Plants of <i>Vicia faba</i> cv. Saraziri

Abstract: Investigation of aberrations caused by gamma radiation in mitosis and meiosis might be fundamental to elucidate the interaction between radiations and biological systems. To identify the effects of the various doses of gamma radiation (25, 35, 45, 55 Gy) on mitotic and meiotic traits and agronomical features, a field experiment and microscopy assays were conducted on M2 generation of Vicia faba cv. Saraziri. Various types of mitotic and meiotic anomalies including laggard chromosomes, precocious movement of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, reduced growth caused by gamma radiation also resulted in auxin reduction, disturbed ascorbic acid content, as well as disturbances in the plant's physiology and biochemical contents. In a previous study on gamma irradiated Vicia faba by Siahpoosh et al (2020), there was a negative correlation between the number of pods per plant and mitosis anomalies, as a higher percentage of mitosis anomalies greatly reduces the number of pods which will affect the seed yield per plant. Clastogenic activities such as sticky chromosomes are caused by either increased contraction or condensation of chromosomes or DNA depolymerization and partial dissolution of nucleoproteins which is irreversible and might lead to apoptosis (Sabeen et al, 2020).…”
Section: Gamma Irradiation Induced Clastogenic Abnormalitiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, reduced growth caused by gamma radiation also resulted in auxin reduction, disturbed ascorbic acid content, as well as disturbances in the plant's physiology and biochemical contents. In a previous study on gamma irradiated Vicia faba by Siahpoosh et al (2020), there was a negative correlation between the number of pods per plant and mitosis anomalies, as a higher percentage of mitosis anomalies greatly reduces the number of pods which will affect the seed yield per plant. Clastogenic activities such as sticky chromosomes are caused by either increased contraction or condensation of chromosomes or DNA depolymerization and partial dissolution of nucleoproteins which is irreversible and might lead to apoptosis (Sabeen et al, 2020).…”
Section: Gamma Irradiation Induced Clastogenic Abnormalitiesmentioning
confidence: 85%
“…Mitotic cells can easily be obtained from the roots of germinating seed which provide an early indicator of plant sensitivity towards the mutagen. The presence of chromosomal aberration in mitotic cells can be used to relate it to GAMMA IRRADIATION INDUCED CLASTOGENIC ABNORMALITIES the possibility of a similar occurrence in meiotic cells as proved by Siahpoosh et al (2020), where similar types of chromosomal aberrations can be observed in mitotic and meiotic cells of gamma irradiated Vicia faba.…”
Section: Gamma Irradiation Induced Clastogenic Abnormalitiesmentioning
confidence: 99%
“…Such indicators as the general rate of chromosomal aberrations and various rates of individual changes in the spectrum were of key importance for determining the nature of the impact on the chromosomal apparatus. Thus, such indicators as the presence of double fragments, bridges, the ratio of fragments and bridges (in terms of the nature of the mutagenic factor), and the presence of complex chromosomal rearrangements were of great importance for the identification of a mutagenic factor at the cell level (Nazarenko, 2016;Siahpoosh et al, 2020). However, the presence of such a number of micronuclei and lagging chromosomes with such a small presence of cells with complex aberrations has never been observed under the action of any chemical substance (Nikolova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%